2022
DOI: 10.3390/polym14030415
|View full text |Cite|
|
Sign up to set email alerts
|

Thiolated Chitosan Microneedle Patch of Levosulpiride from Fabrication, Characterization to Bioavailability Enhancement Approach

Abstract: In this study, a first attempt has been made to deliver levosulpiride transdermally through a thiolated chitosan microneedle patch (TC-MNP). Levosulpiride is slowly and weakly absorbed from the gastrointestinal tract with an oral bioavailability of less than 25% and short half-life of about 6 h. In order to enhance its bioavailability, levosulpiride-loaded thiolated chitosan microneedle patches (LS-TC-MNPs) were fabricated. Firstly, thiolated chitosan was synthesized and characterized by nuclear magnetic reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 76 publications
(91 reference statements)
0
8
0
Order By: Relevance
“…MUC1 expression is reported to be an important molecular marker of cervical squamous cell carcinoma [ 16 ]. Numerous studies confirmed that MUC1 can enhance the proliferation and metastasis of different tumor cells [ 17 19 ]. The cytoplasmic end of MUC1 can be used as a scaffold to activate multiple signal pathways through the activation of specific kinases, including PI3K, Akt, and MAPK [ 20 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…MUC1 expression is reported to be an important molecular marker of cervical squamous cell carcinoma [ 16 ]. Numerous studies confirmed that MUC1 can enhance the proliferation and metastasis of different tumor cells [ 17 19 ]. The cytoplasmic end of MUC1 can be used as a scaffold to activate multiple signal pathways through the activation of specific kinases, including PI3K, Akt, and MAPK [ 20 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…After surgery, due to the decrease of gastrointestinal motion amplitude and degree, an internal hernia or intestinal loop is generated between the intestines, which eventually leads to acute intestinal obstruction [ 13 ]. Clinical treatment of intestinal obstruction is mostly symptomatic treatment and surgical treatment, among which surgical treatment is more stimulating and damaging to the body and prone to postoperative adverse events [ 14 ]. Therefore, the selection of safe and effective treatment means is the focus of the gastroenterology department.…”
Section: Discussionmentioning
confidence: 99%
“…The Higuchi plot is known as a curve drawn between square root of time taken on X axis and cumulative drug release on Y axis. In the Korsmeyer-Peppas plot, a curve was drawn between log time taken on X axis and log percentage cumulative drug release on Y axis [ 40 , 41 ].…”
Section: Methodsmentioning
confidence: 99%